La Ley 100 en la visión de un salubrista: una aproximación en el concepto de la salud como empresa social. - Cruz G., Luis Fernando (Colombia Medica, 1996)
La Ley 100 en la visión de un salubrista: una aproximación en el concepto de la salud como empresa social